The Online Learning Environment: Creating a space for Mauritian women learners - Gokool-Ramdoo, Shushita (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
This paper examines how online distance education acts to democratize access to, and suit the ontologies of, Mauritian women who seek to empower themselves for development. Data from semi-structured interviews of 30 middle class couples are presented in this paper. Interviews and analyses are premised on a feminist perspective and conducted within the social relations analysis framework. The objective of this research was to understand what types of supportive environments (social spaces) enable Mauritian women to engage in educational endeavours that promote their personal potentials and creativities which, in turn, advance democracy for all citizens of Mauritius. Husbands were also interviewed to provide ground for analysis and to decrease bias, which can be generated by women-only data. (1) Marriage/ family and (2) occupation, represent the ‘social spaces’ selected for this study. Discretion, degree of learner control, and the outreach capacity inherent in distance learning makes the online modality a natural choice to democratize women’s access to education. Based on interviewees’ experiences and perceptions, this study concludes that online learning can enhance and democratize women’s access to education for personal development – but only if the power relationships in the two ‘social spaces’ are well understood and well negotiated by these women. The findings in this paper shed light on the importance of understanding ‘learner spaces’ when establishing and setting-up open learning organisations.